Opportunistic screening for genital chlamydial infection. I: Acceptability of urine testing in primary and secondary healthcare settings. Issue 1 (1st February 2003) - Pimenta, J M; Catchpole, M; Rogers, P A; Perkins, E; Jackson, N; Carlisle, C; Randall, S; Hopwood, J; Hewitt, G; Underhill, G; Mallinson, H; McLean, L; et al.
Abstract : Objectives: To determine the acceptability of opportunistic screening for Chlamydia trachomatis in young people in a range of healthcare settings. Design: An opportunistic screening programme (1 September 1999 to 31 August 2000) using urine samples tested by ligase chain reaction (LCR). Data on uptake and testing were collected and in-depth interviews were used for programme evaluation. Setting: General practice, family planning, genitourinary medicine clinics, adolescent sexual health clinics, termination of pregnancy clinics, and women's services in hospitals (antenatal, colposcopy, gynaecology and infertility clinics) in two health authorities (Wirral and Portsmouth and South East Hampshire). Main participants: Sexually active women aged between 16 and 24 years attending healthcare settings for any reason. Main outcome measures: Uptake data: proportion of women accepting a test by area, healthcare setting, and age; overall population coverage achieved in 1 year. Evaluation data: participants' attitudes and views towards opportunistic screening and urine testing. Results: Acceptance of testing by women (16–24 years) was 76% in Portsmouth and 84% in Wirral. Acceptance was lower in younger women (Portsmouth only) and varied by healthcare setting within each site. 50% of the target female population were screened in Portsmouth and 39% in Wirral. Both the opportunistic offer of screening and the method of screening were universally acceptable. Major factors influencing a decision to accept screening were the non-invasive nature of testing and treatment, desire to protect future fertility, and the experimental nature of the screening programme. Conclusions: An opportunistic model of urine screening for chlamydial infection is a practical, universally acceptable method of screening.